Detection and Isolation of Infectious Bovine Rhinotracheitis (IBR) Virus from Clinically Suspected Bovines in Telangana State - Junuthula, Abhilash; Manchikatla, Srinivas; T R, Kannaki; Putty, Kalyani; Ganji, Vishveshwar (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Infectious Bovine Rhinotracheatis (IBR) is a viral disease that causes huge losses to dairy economy by causing abortions and other pathogenic effects resulting in drop of production. IBRV circulates as 2 major subtypes; BoHV-1.1 and BoHV-1.2 associated with respiratory symptoms and genital infections, respectively, in bovines. The present study was taken up to detect and isolate BoHV-1 from field cases using conventional PCR, Real-time PCR, followed by isolation in cell cultures. Total of 125 samples comprising of 31 nasal swabs, 14 serum samples, 10 vaginal swabs, 7 raw semen samples and 63 extended semen samples were collected from IBR suspected animals of various organised dairy farms and semen station of Telangana state. All the samples were subjected for virus detection, followed by isolation studies. Of the 125 samples screened by Real-time PCR, 18 extended semen samples, 2 nasal swabs, 1 vaginal swab, and 1 raw semen sample were found positive for BoHV-1 and all the 14 serum samples were negative, which account for a positivity rate of 17.6%. The positive samples were propagated in MDBK cell lines for isolation of BoHV-1. The signs of CPE were seen on the 5th day of inoculation on third passage. The viral harvest was re-confirmed by real time PCR.